(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
Hydrothermal process was used to prepare CuO nanoparticles. CuO nanoparticles can be prepare without organic solvents, expensive raw materials by a hydrothermal method. XRD diffraction reveals that CuO nanoparticles have a monoclinic structure with particle size 20nm , and AFM analysis showed that the diameter of the Grain size is in a nanometer range. The analysis by FTIR spectra assure that the composition was CuO, and the features of vibrational types of Cu–O were fixed. also the optical properties was analysed with UV–vis showed that CuO nano particles have considerable a blue shift , which have aband gab equal to (4.9 eV ) , and this is because the effect of quntum confienment of prepared CuO nano particles.